Simulation of the Potential Suitable Distribution of the Endangered Cremastra appendiculata in China Under Global Climate Change - Ouyang, Xianheng; Chen, Anliang; Brien Strachan, Garry; Mao, Yangjun; Zuo, Luying; Lin, Haiping (Frontiers in Environmental Science, 2022)
Predicting the spatial distribution of species in relation to suitable areas under global climate change could provide some references for conservation and long-term management strategies for the species. In this study, the MaxEnt was optimized by adjusting the feature combination and regulation magnification parameters with the ENMeval data package. Based on 127 Cremastra appendiculata spatial distribution locations and 14 environmental factors, the potential distribution areas of C. appendiculata under the present and future climate conditions (2050s, 2070s) were simulated, and the dominant environmental factors influencing the spatial distribution of C. appendiculata were analyzed. The feature combination (FC) and the regularization multiplier (RM) were selected as per the Akaike information criteria (AICc). The model showed a complexity and degree of over-fitting (delta AICc = 0, omission rate = 0.106, the difference in the under the under the curve values between the training and testing areas was 0.021) after establishing the optimal model (FC = LQH, RM = 2.5), and the results indicated that the optimal model performed well in simulating the potential spatial distribution of C. appendiculata (the area under the receiver operating characteristic curve = 0.933). The results showed that the suitable habitat of C. appendiculata currently in China is 187.60 × 104 km2, while the highly suitable habitat is 118.47 × 104 km2, the moderately suitable habitat is 53.25 × 10 4 km2, and the poorly suitable habitat is 15.88× 104 km2. There was an increasing trend in suitable habitat of C. appendiculata under six climate scenarios (SSP1-2.6, SSP2-4.5, SSP5-8.5) in the 2050s and the 2070s and that habitat will extend to the northwest as a whole. The highly suitable habitat of C. appendiculata in nature reserves is 0.47 × 104 km2; consequently, there is a large gap in the protection of C. appendiculata. The distribution of C. appendiculata was influenced by the temperature, precipitation and normalized vegetation index.